Structures of the human mitochondrial ribosome bound to EF-G1 reveal distinct features of mitochondrial translation elongation - Ravi Kiran Koripella (Nature Portfolio, 2020)
Translation within mitochondria is carried out by specialized mitoribosomes and translational factors. Here the authors describe cryo-EM structures of the human mitochondrial translation elongation factor G1 in complex with human mitoribosomes, revealing distinct mechanism that include conformational changes at the polypeptide exit tunnel.